Composition and assembly of soil bacterial communities between tidal saltwater and freshwater marshes in China - Kam Tang (Applied Soil Ecology, 2024)
With the increasing salinization of coastal lowlands due to sea level rise, a comprehensive assessment of salinity effects on soil microbial community is crucial for understanding and predicting the corresponding shifts in ecological processes. We compared topsoil bacterial samples from tidal saltwater and freshwater marshes, both dominated by Phragmites australis, in six main estuaries along the tropical-subtropical gradient in China. The bacterial communities in both saltwater and freshwater marshes had similar niche breadths, suggesting similar ability to exploit resources. Salinity difference limited the exchange of bacteria between the two habitats, with only 8.9 % of operational taxonomic units shared between the two communities. Network analysis suggested that the average path length was shorter in the saltwater marshes than the freshwater marshes, and the higher negative cohesion in saltwater marsh networks would enhance the network stability. The assembly of both communities was mostly stochastic, but freshwater marsh communities demonstrated a stronger diffusion restriction than saltwater counterparts. These results suggest that increasing salinization of coastal lowlands will alter the taxonomic and network characteristics of soil microbes, especially in the tidal freshwater marsh, but the stochastic nature of the assembly suggests that the changes may be irreversible.